The Influence of Leadership on Hotel Staff Well-being through HRM Practices and Change Management during the Pandemic in South Kalimantan - Hanifah, Hanifah; Sari, Erini Junita; Arifin, Zainal (STKIP Singkawang, 2025)
This study aims to explain the influence of leadership style on well-being or psychological comfort for hotel employees during the pandemic season through human resource management practices and change management as mediation in a structural equation model (Structural Equation Modelling). The research method used a survey of 137 hotel employees in 46 star hotels in South Kalimantan. Each hotel was represented by 2 or 3 people who had worked for more than 2 years. Using multivariate analysis techniques, SEM (Structural Equation Modelling) was used to measure the relationship between variables and the model. Results showed that transformational leadership had a positive effect on employee well-being, but it will be even better if it is mediated by wise HRM practices and participatory change management. The research implication was that hotel managers must help their employees stay calm, comfortable at work and motivated at work even though they are facing the COVID-19 pandemic. Originality: This study first combined the influence of leadership variables on well-being through HRM practices and change management.